Development of a structural health monitoring system with IoT smart nodes based on mathematical model of inverted pendulums equipped with accelerometers. (11th October 2022) - Scuro, Carmelo; Alì, Giuseppe; Demarco, Francesco; Porzio, Saverio
For centuries, the Italian historical and cultural heritage has been subject to seismic events that have damaged its integrity. The only way to preserve historic centres is to monitor their health through the integration of the traditional structural health monitoring (SHM) system. The aim of the work is to extend the monitoring of historical masonry buildings using an innovative approach based on the simultaneous use of mathematical and finite element models to detect a reduced number of points to be monitored and establish the maximum stress that they can withstand before considering the whole structure in danger. The paper proposes an IoT-based SHM, for the online assessment of the displacement of the control points of a historic structure subject to an earthquake, which minimises the computational burden and reduces construction costs. This will be done by implementing a mathematical model with an inverse pendulum and using it to derive the parameters of interest.